Accelerated development and changes in rainfall trends and variations in Malaysia: a case study of the Kinta River basin 1960-2006 - Mohmadisa Hashim,; Wan Ruslan Ismail,; Zullyadini A. Rahaman,; Nasir Nayan,; Zainudin Othman,; Yazid Saleh, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Environmental impact induced by rapid urbanization and development may be traced from changes in local rainfall trends and variations. This study examined the trends and variations of rainfall in the Kinta River basin, Perak, a region in Malaysia that is rapidly urbanizing and developing. Long-term rainfall data from the year 1960 to 2006 were obtained from the Department of Irrigation and Drainage (DID) involving 15 rainfall stations in the Kinta River basin were employed to analyse long-term variations and precipitation trends. Results of the Mann-Kendall tests show that the Kinta River basin received high rainfall during the Northeast monsoon (950 mm) as compared to that received during the Southwest monsoon (309 mm). The tests also showed that the annual rainfall in the Kinta River basin had an increasing trend from the year 1960-2006 with the value of S=217 as did the monthly rainfall (except in the months of June and July 8) and seasonal rainfall during Northeast monsoon (S = 216) and Southwest monsoon (S = 97). These trends of increasing rainfall appeared to give the early impression that the basin should not have any problems with regard to water supply, in particular, for the purpose of agricultural irrigation and domestic use. However, careful planning should still be undertaken in view of the rapid development of the basin due to rapid urbanisation of the areas surrounding the Ipoh City as there will certainly be growing demand for water in this area in the near future.